On the Effects of Bremsstrahlung Radiation During Energetic Electron Precipitation. Issue 2 (30th January 2018) - Xu, Wei; Marshall, Robert A.; Fang, Xiaohua; Turunen, Esa; Kero, Antti
Abstract: Precipitation of energetic particles into the Earth's atmosphere can significantly change the properties, dynamics, as well as the chemical composition of the upper and middle atmosphere. In this paper, using Monte Carlo models, we simulate, from first principles, the interaction of monoenergetic beams of precipitating electrons with the atmosphere, with particular emphasis on the process of bremsstrahlung radiation and its resultant ionization production and atmospheric effects. The pitch angle dependence of the ionization rate profile has been quantified: the altitude of peak ionization rate depends on the pitch angle by a few kilometers. We also demonstrate that the transport of precipitating electron energy in the form of bremsstrahlung photons leads to ionization at altitudes significantly lower than the direct impact ionization, as low as ∼20 km for 1 MeV precipitating electrons. Moreover, chemical modeling results suggest that the chemical effects in the atmosphere due to bremsstrahlung‐induced ionization production during energetic electron precipitation are likely insignificant. Key Points: The energy and altitude distributions of bremsstrahlung photons produced during electron precipitation have been quantified The ionization rate due to both precipitating electrons and associated bremsstrahlung photons has been calculated Bremsstrahlung‐induced chemical impacts on the atmosphere during realistic electron precipitation are likely insignificant